БАЛАЛАРҒА ҚАРАҚАЛПАҚ ТИЛИН ҮЙРЕТИЎДИҢ ӨЗИНЕ ТӘН ӘҲМИЙЕТИ - Жумашева, Г.; Пердебаева, М.; Утемуратова, Г. (FAN va JAMIYAT, 2017)
The article is devoted to a problem of formation communication skills of children in the Karakalpak language on the basis of principle of succession and continuity of education. In the article it is emphasized the necessity of development of theoretical and methodical bases of teaching the second language with a support on national ideology of independence, activization of speech and intellectual activity of children, involving them to spiritual values of the Karakalpak people.